Catching Common Cold Virus with a Net: Pyridostatin Forms Filaments in Tris Buffer That Trap Viruses—A Novel Antiviral Strategy? - Real-Hohn, Antonio (Viruses, 2020)
The neutrophil extracellular trap (ET) is a eukaryotic host defense machinery that operates by capturing and concentrating pathogens in a filamentous network manufactured by neutrophils and made of DNA, histones, and many other components. Respiratory virus-induced ETs are involved in tissue damage and impairment of the alveolar–capillary barrier, but they also aid in fending off infection. We found that the small organic compound pyridostatin (PDS) forms somewhat similar fibrillary structures in Tris buffer in a concentration-dependent manner. Common cold viruses promote this process and become entrapped in the network, decreasing their infectivity by about 70% in tissue culture. We propose studying this novel mechanism of virus inhibition for its utility in preventing viral infection.